2016
DOI: 10.1021/acs.orglett.6b02469
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Grifolin, Grifolic Acid, LL-Z1272α, LL-Z1272β, and Ilicicolinic Acid A

Abstract: A novel synthetic approach for the synthesis of bioactive phenolic natural products is reported. This strategy highlights the power of halogenative aromatization reactions recently developed in our group for preparing densely functionalized arenes in a controlled fashion. Five natural products related by an aromatic core and a farnesyl side chain are synthesized. In contrast to prior methods, this synthesis features high efficiency and generality that permits preparation of targets in gram-scale quantities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Similarly, ∆ 6′ was deduced as 6′E as shown in Figure 2. Thus, 1 is a new derivative of the co-isolated compound, grifolin (2) [6], and named grifolin B (Figure 1). The NOESY correlations from H-2 to H 2 -4 , H 3 -12 to H 2 -5 , and no observed correlation from H-2 to H 3 -12 confirmed the geometry of ∆ 2 as 2 E. Similarly, ∆ 6 was deduced as 6 E as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, ∆ 6′ was deduced as 6′E as shown in Figure 2. Thus, 1 is a new derivative of the co-isolated compound, grifolin (2) [6], and named grifolin B (Figure 1). The NOESY correlations from H-2 to H 2 -4 , H 3 -12 to H 2 -5 , and no observed correlation from H-2 to H 3 -12 confirmed the geometry of ∆ 2 as 2 E. Similarly, ∆ 6 was deduced as 6 E as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Grifolic acid is a farnesyl phenolic compound first isolated from the mushroom Albatrellus confluens and can be totally synthesized now [ 2 ]. It has been shown that grifolin, an analog of grifolic acid, has inhibitory effects on variety of tumor cells [ 4 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some natural compounds, which are isolated from botany, fungi and marine organism, are putative candidates for antitumor drugs [ 1 ]. It is well known that grifolin, one of the natural compounds isolated from the fresh fruiting bodies of the mushroom Albatrellus confluens [ 2 ], exhibits antitumor effects on nasopharyngeal carcinoma, osteosarcoma, and gastric tumor cells [ 3 5 ]. Grifolic acid (the structure in Additional file 1 ) is a derivative of grifolin, but its effects on tumor cells are not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Diversifiable route to polysubstituted phenolic compounds: Grabovyi and Mohr (2016), West et al (2017, 2018)…”
Section: Structure‐aided Inhibitor Designmentioning
confidence: 99%
“…Grabovyi and Mohr discovered an alternative toward the total synthesis of polysubstituted phenolic natural products featuring terpenoid side chains (Scheme ). This pathway, in which the phenolic head group is introduced early in the synthesis, is advantageous because it uses accessible protecting groups (eg, methoxymethyl, tert‐butyloxycarbonyl, and tert‐butyldimethylsilyl) that are easily cleaved using HCl, ZnBr, and TBAF, respectively, and it allows the gram scale synthesis of the products in high overall yields (>50%).…”
Section: Structure‐aided Inhibitor Designmentioning
confidence: 99%